Modelling the transfer of life from Mars to its moons. (November 2019) - Summers, David
Highlights: Modelling the transfer of mass from Mars to its moons. What effect would the transfer have on Martian Life. How long Martian Life would survive on the Mars moons. What affects the Martian Moons being under Planetary Protection. Abstract: We describe a model of transfer of material from Mars to its moons, and the sterilization that material goes through in that transfer. This is used to gain understanding of if there is viable life on Mars, would that also be on the Martian moons. As Mars is under Planetary Protection, this work looks at should the Martian moons also be under Planetary Protection due to the transfer of unsterilized material.